The naked chef - Oliver, Jamie, 1973- (Penguin Books, 2001)
Britain's most exciting young chef, Jamie Oliver combines bold flavours and fresh ingredients within simple recipes. He is at the cutting edge of modern life and modern British cooking. "The Naked Chef" has something for everyone - from those who want great food but want to keep it simple, to those who work for a living and don't have time to spend all evening cooking. It is about giving people confidence and getting them to feel at ease in the kitchen, even if they have never tried cooking before!